2002
DOI: 10.1002/tl.75
|View full text |Cite
|
Sign up to set email alerts
|

Designing collaborative learning places: Psychological foundations and new frontiers

Abstract: As an alternative to lecture, imagine engaging your students in a collaborative activity during your next class meeting. You divide the class into five small groups and ask each group to solve a problem and present a solution. Anyone who has attempted such a feat can attest to the inadequacy of most college classrooms for supporting group work and the importance of the physical environment in determining the success of collaborative learning. What would the ideal collaborative learning place look like? Brufee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 16 publications
0
31
0
3
Order By: Relevance
“…From the discussion site of the MLE it was observed that there was a large amount of student peer support when any difficulties were encountered 7,8 .…”
Section: Staff End Of Module Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…From the discussion site of the MLE it was observed that there was a large amount of student peer support when any difficulties were encountered 7,8 .…”
Section: Staff End Of Module Evaluationmentioning
confidence: 99%
“…Contrary to the notion that education technology encourages campus based institutions to deliver more of their provision at a distance, research literature suggests that educational technology can have the effect of drawing staff and students closer together, both physically and virtually 7,8 . The authors felt it was important to maintain cohesion within the module and to maintain good communication and dialogue between students and staff.…”
Section: Introductionmentioning
confidence: 97%
“…Entire journals (for instance, the Journal of Asynchronous Learning Networks) have been established to study the use of these media for educational purposes. However, in recent years, a movement within traditional classroom settings to examine the impact of the physical classroom environment on learning has carried over to the online setting, prompting researchers to ponder the effects that different online environments might have on student learning experiences (Graetz & Goliber, 2002). Researchers examining the role that the learning space has in shaping student learning experiences have determined that variations in the physical classroom setting can have a significant impact on student learning experiences and the overall effectiveness of the class (Van Note Chism & Bickford, 2002).…”
Section: The Impact Of Mediamentioning
confidence: 99%
“…Although the potential influence of the physical environment in higher education has been accepted by many scholars (Gee, 2006;Graetz & Goliber, 2002;Jameison, 2003;Jessop, Gubby, & Smith, 2011;Temple 2007Temple , 2009Temple , 2014, information on appropriate physical environment for teacher education is deficient. The education building should be suitable to the field of education.…”
Section: Introductionmentioning
confidence: 99%